Libraries in military schools of the XVIII – beginning the XX century and their role in educating Russian army officers - M. A. Bondarenko (Библиосфера)
The article summarizes materials on the history of formation and development of Military Schools libraries in the Russian Empire. It examines the structure of libraries, normative documents that regulated their activity, compares libraries in the capital's and provincial military schools. Special attention is paid to the role of libraries have in forming creative, scientific and personal features of future officers. Opinions of the former cadets on the impact of libraries and reading on their lives are cited.